A CONCISE ANALYSIS OF THE FOREIGN LANGUAGE EXAMINATION (YDS) IN TURKEY AND ITS POSSIBLE WASHBACK EFFECTS - Erkan Külekçi (Informascope, 2016)
In this paper, some basic information about the Foreign Language Examination (YDS) is presented before the construct of the test is analysed in respect of assessing language proficiency. Then, the issues such as reliability and validity of the test are briefly addressed, and both current and possible outcomes of YDS are discussed. Finally, some suggestions for the future direction are presented as the necessity of using computer/internet assistance and encompassing more areas of language knowledge and language skills are highlighted. While this paper provides a ground for future studies to examine YDS, it is strongly emphasized that further and detailed research with empirical data on the test is necessary in order to reveal a much more accurate examination.